Optimization of biventricular cardiac resynchronization improves cardiac power and atrial kinetics in patients with systolic heart failure with often hospitalizations for decompensation. (3rd October 2022) - Magkas, N; Xydis, P; Konstantinou, K; Antoniou, C; Chrysohoou, C; Manolakou, P; Dilaveris, P; Tsioufis, K
Abstract: : Cardiac resynchronization therapy (CRT) reduces symptoms and improves left ventricular function in patients with heart failure due to left ventricular systolic dysfunction and cardiac dyssynchrony. In this work the biochemical, clinical and echocardiographic outcome of optimizing CRT (optCRT) function by the optimal VTI value of left ventricular outflow track. Methods: 80 NYHA III patients (68±10 years; 75% men; 53% ischemic cardiomyopathy-ICM), under optimal tolerated medical therapy, with standard BVP indication, having been implanted with a CRT system. Echocardiographic measurements, including aortoventricular coupling (VAC) calculation, 6-min-walking-test and quality of life (MLHF questionnaire) were measured at baseline, 6 months on optCRT. Cardiac power (CP) was calculated according the equation: CP=Cardiac Output x Mean Aortic Pressure/451. Results: End-systolic volume of left ventricle was reduced (p=0.001) in both ischemic and non-ICM; while max left atrial volume was reduced only in non-ICM patients (72.1±32 to 65.8±30, p=0.04). Global longitudinal strain was improved in non ICM patients (p=0.015). Systolic strain of right ventricle was improved in non-ICM (9.4±2.2 to 10.7±2.3 vs. 8.7±3 to 8.9±3.2, p=0.03 for non-ICM); while left atrial function and the ratio E to E TDI of mitral annulus were not improved in either group. Non-ICM patients improved VAC (baseline: 1, 36±0, 3; CRT: 1.11±0.2; p=0.01) and CP (baseline 660±160 to 782±260, p=0.001); while no significant improvement was detected to ICM patients. 6-min-walk test was improved up to 30% (p=0.05). NtproBNP levels were decreased only in non-ICM patients (1759±1060.9 to 1015±650 vs. 2063, 8±1800 to 1950.7±2342, p=0.001). MLHFQ improved in non-ICM patients (p=0.015); while non-significant improvement was detected in ICM patients. Conclusion: Optimization of cardiac resynchronization therapy based on stroke volume maximization benefits quality of life and exercise tolerance, mainly in non-ICM. GLPS and aorto-ventricular coupling was improved in non-ischemic patients, reflecting the better adaptation of CRT in this population. Thus, CRT optimization by echocardiographic evaluation may be useful in improve clinical status and quality of life in CRT non-responder patients. Funding Acknowledgement: Type of funding sources: None.